Effect of biochar derived from biogas residue on methane production during dry anaerobic fermentation of kitchen waste. (15th July 2022) - Li, Dongyang; Sun, Mengyang; Xu, Jianfeng; Gong, Tiancheng; Ye, Meiying; Xiao, Yi; Yang, Tianxue
Graphical abstract: Highlights: Biogas residue biochar (BRB) was used as an additive in dry anaerobic fermentation. Methane production and hydrolysis was enhanced by BRB. Microbial diversity increased by BRB. Fastidiosipila, Proteiniphilum and Methanosarcina enriched by BRB. Abstract: Kitchen wastes (KW) dramatically increasing with population and economy enhancing, and dry anaerobic fermentation was used to treat it. However, the large amount of biogas residue severely restricted the application of dry anaerobic fermentation, because the high total solid might lead to the system failure. Therefore, it is urgent to find appropriate way to improve the efficiency of dry anaerobic fermentation and reduce the great amount of biogas residue. In this study, a tentative experiment was conducted to investigate the effect of biochar prepared from biogas residue on the performance of dry anaerobic fermentation system. The results showed that almost half of the biogas residue was reduced and converted into biochar. At the presence of biochar, methane yield was 308.6 mL/gVS, which was 10.5% higher than that of control. Compared to the system without biochar, the highest volatile fatty acid (VFA) concentration was 19.3% higher and the percentage of acetate and valerate was 25.3％ and 12.8％, while it was 16.3% and 22.0% in the control, suggesting that biochar accelerated the degradation of VFA. Bacteria community diversity increased, Fastidiosipila and Proteiniphilum enriched at the presence of biochar, which might accelerate the hydrolysis and acidification of KW. Hydrogenotrophic methanogens was dominated and syntrophic acetate oxidation was the primary pathway to produce methane. This study developed a new recycle route for improving the efficiency of dry anaerobic fermentation while reducing the large amount of biogas residue generated from dry anaerobic fermentation.